2009
DOI: 10.1001/archoto.2009.149
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Predict Postoperative Pulmonary Complications After Supracricoid Partial Laryngectomy

Abstract: Patients 60 years or older and patients with cricohyoidopexy are at high risk of having postoperative pulmonary complications after supracricoid partial laryngectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
(25 reference statements)
0
23
1
Order By: Relevance
“…In contrast to previous studies (1,9,10,1618), the present study has shown that PPCs are not associated with age or surgery duration, however, this may be due to differences in sample size or other factors. Clinical history of previous craniotomy procedures for brainstem and adjacent brainstem tumors is usually considered a contraindication for subsequent elective craniotomies.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies (1,9,10,1618), the present study has shown that PPCs are not associated with age or surgery duration, however, this may be due to differences in sample size or other factors. Clinical history of previous craniotomy procedures for brainstem and adjacent brainstem tumors is usually considered a contraindication for subsequent elective craniotomies.…”
Section: Discussioncontrasting
confidence: 99%
“…The second most frequent complication after supraglottic laryngectomy is aspiration pneumonia. The risk seems to be higher in older patients, therefore, supracricoid or supraglottic laryngectomies are rarely indicated in this group of patients . The reported risk of pneumonia for open approaches ranges from 3.8% to 40% .…”
Section: Discussionmentioning
confidence: 99%
“…The number of arytenoids has been found to be associated with short‐term outcomes such as time to removal of tracheostomy, feeding‐tube, risk of pulmonary complications, and duration of hospitalization, but not to be associated with long‐term voice and swallowing outcomes . In terms of medical comorbidities and the impact on outcomes, pulmonary function in the form of chronic lung disease and smoking status have also been shown to be associated with the risk of pulmonary complications but the presence of other factors such as drinking, smoking, and comorbidities have not been found to be significant predictors of aspiration . Physiologically, arytenoid mobility, mobility of the base of tongue, and the presence of supraglottic tissue are necessary to enable the functional reorganization of a neoglottal sphincter, which allows for competent voice and swallowing …”
Section: Discussionmentioning
confidence: 99%